2008
DOI: 10.1380/ejssnt.2008.130
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayers at Gel/Gel Interface for Ion Channel Recordings

Abstract: We have developed a practical method to produce durable artificial lipid bilayers using a hydrogel-hydrogel interface for ion channel measurements. Bilayers were formed by forcing a hydrogel-bead into contact with the hydrogel layer (hydrogel plate) in a lipid solution. The immediate formation of a bilayer was observed (< 1 s). This allows channel recordings to be repeated more easily and quickly as compared to conventional methods. Currents of various types of channel such as gramicidin, hemolysin and BK-chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…It appears that organic solvent or excess lipid was present in the thick lipid layer and that the two lipid monolayers contacted each other to form the bilayer. Furthermore, it has been observed that bilayer formation proceeds until the membrane forms regardless of the interface. …”
Section: Resultsmentioning
confidence: 99%
“…It appears that organic solvent or excess lipid was present in the thick lipid layer and that the two lipid monolayers contacted each other to form the bilayer. Furthermore, it has been observed that bilayer formation proceeds until the membrane forms regardless of the interface. …”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of recent developments in artificial bilayer platforms with improved robustness and longevity, microfluidic integration, and parallelization, which indicate the potential of this technology to widen its range of applicability. [5][6][7][8][9][10] In particular, artificial bilayers formed through mechanical contact of lipid monolayers at aqueous/oil interfaces or droplets [11][12][13][14] have enabled implementation in microfluidic devices, 15,16 automation, [17][18][19] and arrays. [20][21][22] These developments in artificial bilayer platforms have the potential to make practical their use in pharmaceutical ion channel screening, alongside automated and parallelized patch clamp platforms.…”
Section: Introductionmentioning
confidence: 99%
“…When measuring channel currents of ion channels reconstituted into the solid-supported lipid bilayers, ionic currents passing through membrane proteins and peptides are typically lower than their original value since the lipid bilayer is in direct contact with the substrate blocking ion flow . To overcome this issue, the use of porous membranes or hydrogel layers as the substrate and the addition of a hydrophilic layer such as hydrogel or polymer layer have previously been reported . The porous-membrane-supported lipid bilayer is achieved via the use of small pores; it typically requires cumbersome fabrication skills.…”
mentioning
confidence: 99%